NURSE-LED INTERVENTIONS FOR IMPROVING MEDICATION ADHERENCE IN CHRONIC DISEASES: A COMPREHENSIVE REVIEW - MANAL ABDULRHMAN ALMUTAIRI, AFAF SAWADI ALENAZI, ALYA KULAIB ALDOSSARY, JAMILAH DAKHEEL ALANAZI, HANA ALSOMALI, AISHA SALEH SELAN; TAGHREED ABDULRAZAQ ALHAWSAWI, SANA ABDULLAH ALOTAIBI, ATHEER KHALAF ALENEZI, HALA MOHAMMED ALABDULLAH, ALJWHARAH NASSER ALHAMEDI, HESSA AYIDH ALMUTAIRI, ASHWAQ SAMEER ALMUTAIRI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Medication non-adherence remains a critical global health challenge affecting clinical outcomes, healthcare costs, and patient morbidity and mortality. Nurses play an essential role in addressing this multifaceted problem through evidence-based interventions. This comprehensive review synthesizes current evidence on nurse-led interventions designed to improve medication adherence in patients with chronic diseases. A systematic search of five major databases (MEDLINE, CINAHL, EMBASE, Cochrane Library, SCOPUS) was conducted to identify relevant studies published without temporal restriction. The review incorporated 22 studies involving 5,975 participants. Nurse-led interventions demonstrated statistically significant improvements in medication adherence across various chronic conditions, with particular effectiveness in improving quality of life, reducing anxiety and depression, and enhancing patient self-management capabilities. Key intervention modalities included patient education, motivational interviewing, home-based support, technology-integrated interventions, and multidisciplinary care coordination. However, significant heterogeneity in intervention design, measurement tools, and outcome definitions limits meta-analytic synthesis. This review highlights the critical role of nurses as key stakeholders in chronic disease management and emphasizes the necessity for personalized, multicomponent interventions tailored to individual patient barriers and facilitators. Future research should focus on standardizing adherence measurement, evaluating long-term sustainability of interventions, and examining cost-effectiveness analyses in diverse clinical contexts.